Matter Injection in EU-DEMO: The Preconceptual Design. (19th May 2021) - Ploeckl, B.; Lang, P. T.; Frattolillo, A.; Igitkhanov, Y.; Pégourié, B.; Fable, E.; Day, Chr.; Gliss, C.
Abstract: EU-DEMO will be the next step in Europe after ITER on the path toward a fusion power plant. The matter injection systems have to provide the requested material in order to establish, maintain, and terminate the burning plasma. Their main function is to fuel the plasma, but other tasks are addressed as well like delivering matter for generating sufficient core radiation and divertor buffering. In the preconceptual design phase performed from 2014 to 2020, the matter injection systems, in particular pellet injection and gas injection, have been assessed. This work describes the main findings and state of the art of the matter injection systems at the transition from the preconceptual design phase to the conceptual design phase.